Flatness-based adaptive sliding mode tracking control for a quadrotor with disturbances - Ma, Dailiang; Xia, Yuanqing; Shen, Ganghui; Jia, Zhiqiang; Li, Tianya (Journal of the Franklin Institute, 2018)
In this paper, a flatness-based adaptive sliding mode control strategy is presented to solve the trajectory tracking problem of a quadrotor. According to the differential flatness theory, the typical under-actuated quadrotor dynamics is transformed into a fully-actuated one. Based on this model, backstepping sliding mode controllers are designed to solve the trajectory tracking problem. To improve the robustness to disturbances, extended state observers are applied as a feedforward compensation of disturbances. Moreover, considering the high-order dynamics and possible instability caused by large observer gains, the adaptive method is applied to compensate for the estimation error. The effectiveness of the proposed control scheme is verified in simulations.